Brief Report: Undertreated Midlife Symptoms for Women Living With HIV Linked to Lack of Menopause Discussions With Care Providers. (15th April 2022) - King, Elizabeth M.; Kaida, Angela; Mayer, Ulrike; Albert, Arianne; Gormley, Rebecca; de Pokomandy, Alexandra; Nicholson, Valerie; Cardinal, Claudette; Islam, Shaz; Loutfy, Mona; Murray, Melanie C. M.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Increasingly, women living with HIV are entering menopause (ie, cessation of menses for ≥1 year) and experiencing midlife symptoms. Menopausal hormone therapy (MHT) is first-line therapy for bothersome hot flashes and early menopause (ie, before age 45 years); however, its use in women living with HIV is poorly described. We conducted a cross-sectional assessment of MHT uptake and barriers to use in this group. Setting: This study was conducted across 3 Canadian provinces from 2015 to 2017. Methods: Perimenopausal and postmenopausal women living with HIV (35 years or older) in the Canadian HIV Women's Sexual and Reproductive Health Cohort Study who answered questions related to MHT use were included. Univariable/multivariable logistic regression evaluated factors associated with MHT use, adjusted for age and contraindications. Results: Among 464 women, 47.8% (222 of 464) had a first-line indication for MHT; however, only 11.8% (55 of 464) reported ever using MHT and 5.6% (26 of 464) were current users. Only 44.8% had ever discussed menopause with their care provider despite almost all women having regular HIV care (97.8%). African/Caribbean/Black women had lower unadjusted odds of MHT treatment compared with White women [odds ratio (OR) 0.42 (0.18–0.89); P = 0.034]. Those who had discussed menopause with their care provider had higher odds of treatment [OR 3.13 (1.74–5.86); P < 0.001]. In adjusted analyses, only women having had a menopause discussion remained significantly associated with MHT use [OR 2.97 (1.62–5.61); P < 0.001]. Conclusion: Women living with HIV are seldom prescribed MHT despite frequent indication. MHT uptake was associated with care provider–led menopause discussions underscoring the need for care provider education on menopause management within HIV care.